Buspirone for the Treatment of Generalized Anxiety Disorder in Down Syndrome: 3 Cases. Issue 1 (January 2022) - Howe, Yamini J.; Thom, Robyn P.; Notson, Erin E.; McDougle, Christopher J.; Palumbo, Michelle L.
ABSTRACT: Objective: Reports on the pharmacologic treatment of anxiety, including generalized anxiety disorder (GAD), in individuals with Down syndrome (DS) are lacking. Methods: We present the case histories of 1 adolescent and 2 young adults with DS and the treatment course of comorbid GAD with buspirone. Results: Treatment with buspirone was safe and well-tolerated and resulted in sustained improvement in symptoms of anxiety for a minimum of 2 years in all 3 cases. Conclusion: Buspirone's generally benign adverse effect profile makes it well suited for treating anxiety in individuals with DS in light of their common medical comorbidities.